A growing captive population erodes the wild Red-crowned Cranes (Grus japonensis) in China. Issue 1 (December 2016) - Zhou, Daqing; Xia, Xin; Xu, Wanggu; Zhang, Haonan; Qian, Zhedong; Gao, Jun; Wang, Zhi; Jiang, Mingkang
Abstract Background The Red-crowned Crane (Grus japonensis ) is an endangered bird species and while the wild population continues to decrease in China, the captive population has dramatically increased over the last two decades. We hypothesized that some of the captive Red-crowned Cranes originated from the wild and that a growing captive population is eroding the wild population in China. Methods We surveyed the size of the population and determined the average annual growth rate, reproductive success rate and mortality rate of captive Red-crowned Cranes in 2013 in China. We assessed this erosion effect through mathematical models, in which the size of the captive Red-crowned Crane population was determined from the annual growth rate, the reproductive success rate and the rate of mortality. Results We found there were a total of 1520 captive Red-crowned Cranes in 2013 in China, with an average annual growth rate of 7.46%, a reproductive success rate of 9.17% and a mortality rate of 3.6%. We found that approximately 10‒27 supplementary Red-crowned Cranes per year and a total of 244, over the 14 year period from 1999 to 2013, were needed to account for the growing captive population in China. Conclusion We conclude that the 244 birds probably came from the wild by taking eggs and capturing juveniles or adults and hence accepted the hypothesis. Perhaps more surprisingly, our annual estimate of the number of supplementary Red-crowned Cranes in captive populations is very conservative, with the erosion effect substantially underestimated, because the total number of captive Red-crowned Cranes in 2013 was underestimated, with the annual reproductive success rate in zoos overestimated. The existence of an erosion effect provides a new perspective for the interpretation of why the Red-crowned Crane population in the wild continues to decrease. In our opinion, it is important to understand the consequences of this erosion effect on the management and conservation of this endangered bird species in China.